ARMC5 Primary Bilateral Macronodular Adrenal Hyperplasia Associated with a Meningioma: A Family Report. (2nd September 2020) - Ferreira, M. J.; Pedro, J.; Salazar, D.; Costa, C.; Aragão Rodrigues, J.; Costa, M. M.; Grangeia, A.; Castedo, J. L.; Carvalho, D.
Abstract : Primary bilateral adrenal macronodular hyperplasia is characterized by functioning adrenal macronodules and variable cortisol secretion. Familial clustering suggests a genetic cause that has been confirmed with the identification of some genetic mutations, including inactivating germline mutations, in armadillo repeat containing 5 (ARMC5) gene. The identification of the pathogenic variant enables the physician to identify and treat these patients earlier and more effectively. It has also been noticed that patients with germline causative variants show a different clinical spectrum, presenting specific clinical characteristics, as the association with the presence of meningiomas.